Arthroscopic Stabilization of Chronic Acromioclavicular Joint Dislocations: Triple- Versus Single-Bundle Reconstruction. (February 2016) - Tauber, Mark; Valler, Dennis; Lichtenberg, Sven; Magosch, Petra; Moroder, Philipp; Habermeyer, Peter
Background: Arthroscopically assisted single-bundle (SB) or double-bundle coracoclavicular (CC) ligament reconstruction using autologous tendon grafts has been reported to provide acromioclavicular (AC) joint (ACJ) stability in chronic instability cases. Recently, additional AC ligament reconstruction to provide triple-bundle (TB) stabilization has been introduced but lacks a comparison of clinical and radiological outcomes. Hypothesis: Arthroscopically assisted anatomic TB CC and AC reconstruction yields superior clinical and radiological results when compared with nonanatomic SB CC reconstruction. Study Design: Cohort study; Level of evidence, 2. Methods: Twenty-six patients (mean [±SD] age, 46.9 ± 12.8 years) suffering from chronic high-grade ACJ instability underwent ACJ stabilization using autologous hamstring grafts. Twelve patients underwent combined anatomic TB CC and AC reconstruction using a semitendinosus tendon with clavicular interference screw fixation (TB group), and 14 underwent isolated SB CC reconstruction using the AC GraftRope system with a gracilis tendon (SB group). After a minimum follow-up of 2 years (mean, 29.0 ± 7.4 months), patients were evaluated radiologically and clinically using the Constant, American Shoulder and Elbow Surgeons (ASES), Taft, and Acromioclavicular Joint Instability Score (ACJI) outcome measures. Results: The mean Constant score increased significantly in both groups, from 71.6 preoperatively to 88.8 postoperatively in the TB group and from 67.8 to 82.6 in the SB group ( P ≤ .009). No intergroup difference was found regarding the final Constant or ASES scores. Regarding the ACJ-specific scores, the final outcomes were significantly different: 10.9 (TB group) versus 9.0 (SB group) for the mean Taft score ( P = .018) and 84.7 versus 58.4, respectively, for the mean ACJI score ( P = .0001). No significant radiological difference was found regarding the mean CC distance (10.7 mm [TB group] vs 13.1 mm [SB group]). The TB group showed superior horizontal ACJ stability ( P = .011), which was associated with a better clinical outcome according to the ACJI and Taft scores. In the SB group, the rate of ACJ instability recurrence was higher (21% vs 8% [TB group]). Conclusion: Combined arthroscopically assisted anatomic TB CC and AC ligament reconstruction using an autologous semitendinosus tendon graft provides superior clinical and radiological results compared with isolated nonanatomic SB CC ligament reconstruction using the AC GraftRope system. In particular, the TB technique can better restore horizontal ACJ stability, which is associated with superior ACJ-specific outcome scores.